At Risk and Underserved: Veterans Treatment Court Team Member Perspectives on Service Delivery Challenges - Kras, Kimberly Raye (Victims & offenders, 2024)
As Veterans Treatment Courts (VTC) proliferate across the United States, questions have been raised about their capacity to provide critical services and support for justice-involved veterans. The current study examines the key decisions made by core VTC team members as justice-involved veterans move through each stage in the VTC process. This study presents in-depth interviews with 145 VTC team members from 20 court jurisdictions across the United States. Interviews revealed common challenges in meeting the service needs of VTC participants coalescing around five intercepts addressing challenges related to pre-entry, eligibility, service coordination and access, and veteran engagement. VTC team members’ views about how best to provide services and support to justice-involved veterans are also highlighted. This study provides the unique perspectives of VTC team members on how to address these challenges in ways that will enhance their ability to offer services and provide support for justice-involved veterans.